2014
DOI: 10.1088/0067-0049/213/1/9
|View full text |Cite
|
Sign up to set email alerts
|

The Catalina Surveys Periodic Variable Star Catalog

Abstract: With the discovery of the first transiting extrasolar planetary system back in 1999, a great number of projects started to hunt for other similar systems. Because the incidence rate of such systems was unknown and the length of the shallow transit events is only a few percent of the orbital period, the goal was to monitor continuously as many stars as possible for at least a period of a few months. Small aperture, large field of view automated telescope systems have been installed with a parallel development o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
494
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 461 publications
(527 citation statements)
references
References 129 publications
18
494
1
Order By: Relevance
“…This relation was derived from 100 000 isotropically selected sources that exhibited no significant sign of variability based on their Welch-Stetson variability index. However, errors at the brighter magnitudes are overestimated and those at fainter magnitudes (>18) are underestimated (Palaversa et al 2013;Drake et al 2014;Vaughan et al 2016). We have derived a multiplicative correction factor from CRTS observations of 350 000 sources in the Stripe 82 Standard Star catalogue (Ivezic et al 2007) that ensures that the mode of the reduced chi-squared variability in magnitude bins of width of mag = 0.05 is centred at unity (see Fig.…”
Section: Catalina Real-time Transient Surveymentioning
confidence: 99%
“…This relation was derived from 100 000 isotropically selected sources that exhibited no significant sign of variability based on their Welch-Stetson variability index. However, errors at the brighter magnitudes are overestimated and those at fainter magnitudes (>18) are underestimated (Palaversa et al 2013;Drake et al 2014;Vaughan et al 2016). We have derived a multiplicative correction factor from CRTS observations of 350 000 sources in the Stripe 82 Standard Star catalogue (Ivezic et al 2007) that ensures that the mode of the reduced chi-squared variability in magnitude bins of width of mag = 0.05 is centred at unity (see Fig.…”
Section: Catalina Real-time Transient Surveymentioning
confidence: 99%
“…In Drake et al (2013a,b) and Torrealba et al (2015), we targeted type-ab RR Lyrae variables, and later extended our search to investigate all types of periodic variable sources in CSS data. In Drake et al (2014a;DR14 hereafter), we explored the Northern data (δ > −20 • , hereafter CSS-N).…”
Section: Introductionmentioning
confidence: 99%
“…Since binary light curves are normally represented by two sine waves, therefore, multiplying the period by a factor of two gives the true period of the binary system. We therefore assigned a period of 0.266402±0.000018 days for the binary system, which is in accordance with the period obtained by Drake et al (2014). In the following equation, we draw the ephemeris for the minimum light as a function of the binary star.…”
Section: Orbital Period Investigationmentioning
confidence: 80%
“…Drake et al (2014) first reported this star as a W UMa contact binary having a period of 0.266398 days and reported a V band amplitude of 0.54 mag. In our analysis, we carried out period analysis using Period04 (Lenz & Breger 2005).…”
Section: Orbital Period Investigationmentioning
confidence: 99%
See 1 more Smart Citation